Using photovoice to engage underserved children with neurodevelopmental disorders and their caregivers in health research: a mixed methods systematic review - Gonzalez, Miriam; Yoo, Paul Y.; Noyek, Samantha E.; MacLeod, Brooke; Kee, Michelle; Phoenix, Michelle; Micsinszki, Samantha K.; Knutson, Marion; Neilson, Christine J.; Woodgate, Roberta L. (Frontiers in Rehabilitation Sciences, 2025)
IntroductionLimited guidance exists for researchers wanting to use photovoice to engage children with neurodevelopmental disorders (NDDs), 0-25 years, and their caregivers in health research. This mixed-methods systematic review synthesized photovoice research with this population with attention to children and caregivers from diverse backgrounds. Diversity of study participants, research areas that have used photovoice with this population, feasibility considerations (adaptations, contextual considerations, practicality), and recommendations provided by study authors were of interest.MethodsWe searched five databases and limited the search to English or French language publications. Eighteen studies met the inclusion criteria. We used a convergent integrated synthesis approach as well as qualitative content analysis to synthesize data from included studies.ResultsThe majority of children and caregivers in selected studies were white. Selected studies focused primarily on autism spectrum disorder (n = 12) followed by intellectual disability (n = 3). Photovoice has been used across six research areas relevant to individual, interpersonal, and organizational level influences on an individual's life. Authors of selected studies faced various contextual considerations (e.g., requiring flexibility) and made adaptations (e.g., using smiley/sad faces to monitor assent) to facilitate research participation. Authors reported photovoice as valuable and useful and provided implementation recommendations (e.g., work one-on-one with participants) and future research directions (e.g., using photovoice with nonverbal children) to advance the use of this methodology.DiscussionOur findings support using photovoice to explore the lived experience of this population, provide guidance to health and rehabilitation researchers seeking inclusive, person-centred approaches to engaging participants in research, and have direct implications for practice.Systematic Review Registrationhttps://osf.io/3xsak/